2017
DOI: 10.1038/ejcn.2017.28
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal and subcutaneous abdominal fat as predictors of cardiometabolic risk in a sample of Mexican children

Abstract: In this sample of Mexican schoolchildren, TBF and SAF, but not IAF, were associated with higher cardiometabolic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…In addition, the associations of SAT were even stronger than those for VAT for most risk factors, especially in boys. Similar results have been reported in several prior small studies 11–13 26 27. A recent study of 94 Mexican school children showed magnetic resonance-measured SAT rather than VAT was associated with higher cardiometabolic risk 11.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, the associations of SAT were even stronger than those for VAT for most risk factors, especially in boys. Similar results have been reported in several prior small studies 11–13 26 27. A recent study of 94 Mexican school children showed magnetic resonance-measured SAT rather than VAT was associated with higher cardiometabolic risk 11.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results have been reported in several prior small studies 11–13 26 27. A recent study of 94 Mexican school children showed magnetic resonance-measured SAT rather than VAT was associated with higher cardiometabolic risk 11. Another small cross-sectional study of 30 overweight and obese prepubertal children reported that insulin sensitivity was negatively correlated with DXA-measured SAT but not with VAT 26.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Fat distribution in different adipose tissue areas is one of the major contributing factor in insulin resistance and metabolic disorders in obesity. There is a growing body of evidence, supporting the leading role of subcutaneous adipose tissue in the development of insulin resistance and meta-inflammation in obesity, as this fat depot is a major source of systemic free fatty acid flux 49 51 . Vieira et al .…”
Section: Discussionmentioning
confidence: 99%